Workshop Berbasis Pengembangan Diri untuk Meningkatkan Motivasi dan Kinerja Guru SD di Kabupaten Barru - Usman Usman; Abdul Majid; Ritha Tuken; Jonathan S Pasinggi; M. Asri B (Yayasan Literasi Sains Indonesia, 2026)
Self-development–based workshops are considered an effective strategy to enhance teachers’ motivation and performance at the elementary school level. This community service program aimed to improve both intrinsic and extrinsic motivation of teachers and to strengthen their professional commitment in implementing quality learning practices in Barru Regency. The identified problems included low work motivation, limited professional self-reflection, and suboptimal teacher performance in lesson planning and instructional implementation. The program employed a participatory approach consisting of needs assessment, material presentation, self-reflection sessions, group discussions, simulations, and evaluation. A total of 35 elementary school teachers from several schools in Barru Regency participated in the workshop. The results indicated an increase in teachers’ understanding of continuous self-development, improved work motivation, and positive changes in attitudes toward enhancing instructional quality. Evaluation through questionnaires and observations showed an improvement in motivation scores and teacher performance indicators after the workshop. The program contributed positively to strengthening professional awareness and fostering a more productive work culture within schools. In conclusion, self-development–based workshops are effective in improving the motivation and performance of elementary school teachers in Barru Regency. It is recommended that such programs be implemented continuously as part of local teacher professional development strategies.